Pengujian konsep psikoterapi unconditional positive regard pada mahasiswa perempuan - Beatriks Novianti Kiling-Bunga; Indra Yohanes Kiling (Program Studi bimbingan Konseling PPs UNM Makassar, 2016)
One of the psychotheraphy approaches that has given positive contributions to the psychiatry is Carl Rogers Client-Centered approach. One of three main conditions that Rogers emphasizes in the approach is Unconditional positive regard. The main condition is called as the curative factor of client-centered theraphy. The article is discussing the study process of unconditional positive regard concept in a person which the sample is the female students. Questions and process flow scheme are also discussed in this article. The study concept is regarded to be able to contribute knowedge to the counseling practitioners in case of facing the student’s problem.